Carol Ann Duffy Poet for Our Times - Dowson, Jane.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This is the only monograph to consider the entire thirty-year career, publications, and influence of Britain's first female poet laureate. It outlines her impact on trends in contemporary poetry and establishes what we mean by 'Duffyesque' concerns and techniques. Discussions of her writing and activities prove how she has championed the relevance of poetry to all areas of contemporary culture and to the life of every human being. Individual chapters discuss the lyrics of 'love, loss, and longing'; the socially motivated poems about the 1980s; the female-centred volumes and poems; the relationship between poetry and public life; and poetry and childhood and written for children. The book should whet the appetite of readers who know little of Duffy's work to find out more, while providing students and scholars with an in-depth analysis of the poems in their contexts. It draws on a wide range of critical works and includes an extensive list of further reading.
1.Poet for Our Times -- 2.Lyrics of Love, Loss, and Longing -- 3.Voices from The 1980s and After -- 4.Words Between Women -- 5.Poetry and the Public Sphere -- 6.Poems about and for Childhood -- 7.Bibliography.
Keywords: Literature, Modern-20th century; Poetry and Poetics